The Ability to play table tennis is determined from the results of hand-eye coordination: Kemampuan Bermain Tenis Meja Ditentukan Dari Hasil Koordinasi Mata-Tangan - Zubir, Zubir Darmawan; Putra, Muarif Arhas; Putra, Riwaldi (Journal Of Sport Education and Training, 2024)
This study aimed to determine whether there was or not a relationship between eye-hand coordination to table tennis ability at SMA Negeri 3 Tambusai. The number of population to know the amount to be taken as a sample will determine the results to be obtained. The sampling technique in this study was total sampling, namely students who took part in table tennis extracurricular activities at SMA Negeri 3 Tambusai consisting of 10 people and the data taken in this study was a technique where all members of the population were sampled. Based on the results of the analysis above, it can be understood that Eye-Hand Coordination was related to Ability in Playing Table Tennis, this occurs when extracurricular Participants remain focused on one goal, so that Eye-Hand Coordination and Ability to Play Table Tennis remain related. So it can be concluded that there was a link between Eye-Hand Coordination and the ability to play table tennis as evidenced by the value of rcalculate = 0.640 > rtable = 0.632 which showed that there was a significant relationship.